Postoperative cardiogenic shock secondary to Takotsubo's syndrome. Issue 12 (31st December 2019) - Dessain, Tessa; Stewart, Rachel; Patil, Shashank
Abstract : Takotsubo's syndrome is a rare acute reversible heart failure, where the pathophysiology is not fully understood. It is being increasingly diagnosed in varied clinical contexts, which can result in atypical presentations in the context of surgical or anaesthetic stress. We discuss the case of a 22-year-old woman who developed cardiogenic shock and impaired left ventricular function after an elective gynaecological procedure. She had a rapid recovery and a follow-up cardiac MRI confirmed Takotsubo's syndrome.